The Effect of Primary Fixation with Standard Postfixation and the Duration of Hydrolysis on Nuclear Features in Image Cytometry - Margareta Fležar; Alexei Doudkine; Marija Us-Krašovec (Analytical Cellular Pathology)
The effect of three primary fixation procedures, used in the preparation of routine cytological samples: air-drying, Delaunay, and Saccomanno fixation, with postfixation in modified Böhm–Sprenger fixative, on nuclear features as a function of hydrolysis time is reported. Three different cell types: lymphatic cells (tonsil), epithelial cells (buccal mucosa) and mesenchymal cells (uterine myometrium) were used for the study. Our findings show, that generally not all features have the same plateau times as the IOD (integrated optical density), and that many features show different values depending on cell type and fixation method. It is therefore recommended that for any primary fixative used in routine clinical work and for each cell type, the hydrolysis curve for all nuclear features to be used in sample analysis should be established.